The Adaptor Protein Crk Controls Activation and Inhibition of Natural Killer Cells - Liu, Dongfang (2012)
Natural killer (NK) cell inhibitory receptors recruit tyrosine phosphatases to prevent activation, induce phosphorylation and dissociation of the small adaptor Crk from cytoskeleton scaffold complexes, and maintain NK cells in a state of responsiveness to subsequent activation events. How Crk contributes to inhibition is unknown. We imaged primary NK cells over lipid bilayers carrying IgG1 Fc to stimulate CD16, and human leukocyte antigen (HLA)-E to inhibit through receptor CD94-NKG2A. HLA-E alone induced Crk phosphorylation in NKG2A(+) NK cells. At activating synapses with Fc alone, Crk was required for the movement of Fc microclusters and their ability to trigger activation signals. At inhibitory synapses, HLA-E promoted central accumulation of both Fc and phosphorylated Crk, and blocked the Fc-induced buildup of F-actin. We propose a unified model for inhibitory receptor function: Crk phosphorylation prevents essential Crk-dependent activation signals and blocks F-actin network formation, thereby reducing constraints on subsequent engagement of activation receptors.